NEW ROLES FOR INDUSTRIAL ENGINEERS IN DEVELOPING COUNTRIES - Lister, G.; Donaldson, K. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: Current industrial engineering paradigms aim to improve quality and profits, and emphasise labour-reduction, specialisation, analysis and optimisation. This can be at odds with the needs in a developing country. We suggest that the emphasis of industrial engineering be re-orientated to support employment growth, the identification of new products and services, education, and training. Pedagogical methods and computer usage should satisfy the needs of such environments. It is not argued that uneconomic and non-competitive processes should be tolerated, rather that activities, which protect and increase employment levels, should be emphasised. Experiences in Kenya and South Africa are used to support this hypothesis. AFRIKAANSE OPSOMMING: Huidige Bedryfsingenieursweseparadigmas beoog om kwaliteit en wins te verbeter en plaas die klem op arbeidsvermindering, spesialisasie, analise en optimisasie. Hierdie tendens is waarskynlik strydig met die behoeftes van ontwikkelende lande. Ons voorstel is dat die fokus van Bedryfsingenieurwese verskuif moet word om indiensnemingsgroei te bewerkstellig, te help met die identifisering van nuwe produkte en dienste, onderwys te bevorder en opleiding te verskaf. Pedagogiese metodes en rekenaargebruik behoort die behoeftes van hierdie omgewings te bevredig. Die argument is nie dat onproduktiewe en nie-mededingende prosesse verduur moet word nie, maar dat die aktiwiteite wat indiensnemingsvlakke verhoog en beskerm, beklemtoon moet word. Eksperimente in Kenia en Suid-Afrika sal gebruik word om hierdie hipotese te ondersteun.